2021
DOI: 10.1080/21655979.2021.1989969
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-877-5p exerts tumor-suppressive functions in prostate cancer through repressing transcription of forkhead box M1

Abstract: The study aimed to investigate the significant potential role of miR-877-5p in Prostate cancer. The expression levels of miR-877-5p and forkhead box M1 (FOXM1) mRNA were detected by qRT-PCR. The prognostic significance of miR-877-5p in prostate cancer was investigated using Kaplan Meier analysis. Then, Cell Counting Kit-8 (CCK-8) and transwell assay were used to evaluate the effects of miR-877-5p on cell biological functions. The mechanism of miR-877-5p action on prostate cancer cells was investigated by lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recent studies have reported that the dysregulation of miRNA expression profiles is associated with PC and emerged as a novel biomarker and potential therapeutic target for the treatment of PC ( 33 , 36 , 37 ). According to the report, miR-877-5p may act as a suppressor in PC and reduces cancer cell proliferation, migration and invasion by targeting FOXM1 ( 38 ). miRNA-125b has been attributed as an oncogene in the pathogenesis of PC through down regulation of Bak1 ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the dysregulation of miRNA expression profiles is associated with PC and emerged as a novel biomarker and potential therapeutic target for the treatment of PC ( 33 , 36 , 37 ). According to the report, miR-877-5p may act as a suppressor in PC and reduces cancer cell proliferation, migration and invasion by targeting FOXM1 ( 38 ). miRNA-125b has been attributed as an oncogene in the pathogenesis of PC through down regulation of Bak1 ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al uncovered that miR-877-5p restrains PDAC progression via negatively regulating lncRNA NR2F1-AS1 [ 45 ]. Additionally, researchers have confirmed miR-877-5p as a positive element in other malignancies [ 46 , 47 ]. Herein, we firstly reported the involvement of miR-877-5p in CML.…”
Section: Discussionmentioning
confidence: 99%
“…The cell proliferation capacity of PCa cells transfected with Oe-TMEM100 or co-transfected with sh-GATA5 was measured using a CCK-8 assay [ 21 ]. Briefly, transfected DU145 cells were seeded into 96-well plates at a density of 5 × 10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%